The spectrum of bone disease in 200 chronic hemodialysis patients: a correlation between clinical, biochemical and histological findings - Duarte, Maria Eugênia Leite (1998)
INTRODUCTION: Renal osteodystrophy includes the complete range of mineral metabolism disorders that affect the skeleton in patients with chronic renal failure. PATIENTS AND METHODS: 200 patients with end-stage renal disease and on dialysis were investigated regarding the clinical, biochemical and histological findings of bone disease. RESULTS: The spectrum of renal osteodystrophy consisted mainly of high turnover bone lesions (74.5%), including osteitis fibrosa in 57.5%. Patients with mild bone disease were on dialysis for shorter periods of time and were mostly asymptomatic. Patients with aluminum-related bone disease (16.5%) had the greatest aluminum exposure, either orally or parenterally, and together with patients with high turnover mixed disease, were the most symptomatic. Although on a non-regular basis, the vast majority of the patients (82.5%) had been receiving vitamin D. The incidence of adynamic bone disease was high (n=8) among parathyroidectomized patients (n=12). Significantly higher serum levels of alkaline phosphatase were observed in osteitis fibrosa. CONCLUSIONS: The use of calcitriol and phosphate-binding agents on a non-regular basis seems to be the reason for the apparent reduced response to the treatment of secondary hyperparathyroidism. Alkaline phosphatase has been shown to be a fair marker for bone turnover in patients with osteitis fibrosa. The severity of the clinical manifestations of bone disease correlates with the histological features of bone lesion and to the time spent on dialysis.